Policing and CBRN hazards: advancing CBRN competence in police education - Wengler, Patrick (Innovations in policing, 2023)
"This book makes an important contribution to police scholarship by focusing on the critical need for law enforcement personnel to receive education on chemical/biological/radiological/nuclear (CBRN) hazards. Under the CBRN umbrella are chemical warfare agents, toxic industrial chemicals, biologically derived toxins, radiological particulate hazards, and other agents, any of which have the potential to inflict bodily harm, incapacitation, or death. Such weapons have been a part of human history for centuries, starting with biological warfare, later shifting over to chemical warfare, and in the last century, radiological and nuclear warfare. The greater availability and accessibility of such materials necessitates that first response and investigation is no longer limited to the military but is required of police forces reacting to incidents in the community, whether acts of terrorism, traffic accidents, or standard industrial incidents. In this book it is argued that basic knowledge of CBRN is essential for police officers at all levels to assess and protect crime scenes, as well as to investigate cases involving CBRN materials. The author uses case studies and technical education to instruct police on how and when CBRN agents can be used maliciously, and the best methods for identifying, analyzing, monitoring, and investigating related incidents. The text makes a clear case for integrating CBRN studies into police education so that first responders are enabled to assess incidents and share information with emergency management and other services to determine the most effective equipment and personnel to deploy. This book is essential for police educators and trainers in both universities and police academies, those administering or engaged in in-service police training, and scholars studying policing, criminal justice, and terrorism"--